The investigation of PV systems quantum efficiency in various irradiation condition. (May 2021) - Swatowska, Barbara; Panek, Piotr; Stapinski, Tomasz
Graphical abstract: Highlights: Variable light conditions and temperature have key meaning for efficiency of photovoltaic conversion. The variation of PV module electrical parameters, mainly EQE and Isc were investigated. The incidence angle of direct radiation strongly influences the cells photocurrent. The lower reduction of Isc were observed for modules structure with ARC2 on glass. Abstract: We confirm the importance of the angle of incidence of direct solar radiation on external quantum efficiency of solar mini-modules consisting of the following closed structure: silicon solar cells with antireflective coating (Si + ARC1)/EVA (ethylene–vinyl acetate) foil /glass with or without antireflective coating (ARC2). The results are consistent with a proposed model of an optical module with a specific architecture. A study of the electrical parameters of photovoltaic modules as a function of the angle of incidence of radiation was carried out using a solar class AAAA simulator. The changes in short circuit current Isc were calculated relative to Isc for the module fully illuminated by light perpendicular to the surface. A decrease in Isc was recorded for modules containing textured glass or Flat glass. The use of antireflective coating ARC2 on glass in module structure increases external quantum efficiency and photogeneration current under AM1.5 global spectrum at 1000 W/m 2 light intensity at temperature 25 °C, mainly for the angle of incidence of 35°.